FVR : through the years - Cal, Ben (Quezon City, Philippines : Philippine Academy for Continuing Education and Research, 1997)
Ben Cal's book is a product of long years of observing its subject and the circumstances of his time and life. It is a tour of a landscape treaded by Fidel Ramos, from soldier to President. He has woven a rich fabric of ideas, conditions and personalities around the man who rose to the leadership of the nation under most historic circumstances.
An officer and a gentleman -- Defender of democracy -- National builder, statesman -- The Peacemaker -- The Lighter side of FVR
Includes index.
Keywords: RAMOS, FIDEL V, -- 1928- PHILIPPINES -- POLITICS AND GOVERNMENT -- 1986-